Leadership and student learning in higher education - Woyu, Fabian (2014)
Motivated by the many schools the Presbyterian Church in Cameroon has from primary, post primary and recently a university, I as a member of the academic family join many to acquire leadership skills useful to the students. The goal to influence the students academically and morally calls for much investment in leadership. More so, as a young university, older universities can serve as lenses for our leadership insight. Hence, the research is done in a Finnish university. The research intends to have an in-depth knowledge of how various leadership roles in a university influence student learning. A qualitative method of research has been considered for these findings, using the semi-structure interview method for data collection. Interviews have been done with some staff members who are either faculty/departmental leaders or teaching staff. A qualitative thematic analysis has been used for this process. Five prominent themes that showed different leadership roles were as follows: the role of the stake holder, the leadership role at the university level, leadership roles of the faculty, departmental level, and the role of the teaching staff. The roles paved the way for the sources enhancing student learning. In a nutshell, leadership roles in universities affect student learning directly or indirectly while the intrinsic source of motivation remains as the responsibility of the student. Administrative staff influence students more indirectly while the teaching staff does it more directly.